2004
DOI: 10.1590/s0001-37652004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Permian plants from the Chutani Formation (Titicaca Group, Northern Altiplano of Bolivia): I. Genera Pecopteris and Asterotheca

Abstract: Fossil plants belonging to the morphogenera Glossopteris, Pecopteris and Asterotheca were collected from the upper part of the Chutani Formation (Titicaca Group), near the town of San Pablo de Tiquina, on the southeastern shore of Lake Titicaca (northern Altiplano, Bolivia). Here we report the analysis of fern-type foliage found at this location. Three species of pecopterid fronds are identified: Pecopteris dolianitii Rohn and Rösler, P. cf. P. cadeadensis Rohn and Rösler, and P. cf. P. pedrasica Read. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
2
12
0
8
Order By: Relevance
“…The only species of Pecopteris confirmed in the first part of this study, i.e. P. dolianitii Rösler and Rohn (see Vieira et al 2004), was previously reported from the Late Permian beds of the Rio do Rasto and Estrada Nova formations in the Paraná Basin (southern Brazil). Therefore, a Late Permian age is proposed for the fossil plant-bearing beds of the Chutani Formation based on the analyzed assemblage.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…The only species of Pecopteris confirmed in the first part of this study, i.e. P. dolianitii Rösler and Rohn (see Vieira et al 2004), was previously reported from the Late Permian beds of the Rio do Rasto and Estrada Nova formations in the Paraná Basin (southern Brazil). Therefore, a Late Permian age is proposed for the fossil plant-bearing beds of the Chutani Formation based on the analyzed assemblage.…”
Section: Introductionsupporting
confidence: 71%
“…The pecopterid foliage corresponds to taxa considered endemic of the Paraná Basin, in southern Brazil (see the first part of this report; Vieira et al 2004). Pecopteris cf.…”
Section: Age Of Floramentioning
confidence: 99%
See 3 more Smart Citations